2017
DOI: 10.3390/ijerph14070817
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Quality in Pregnant Women: A Cross-Sectional Survey in China

Abstract: Objectives: Good maternal health and fetal development require sufficient and good quality of sleep during pregnancy. This study investigated sleep duration and quality in pregnant women, assessing factors with possibly influence on sleep. Method: A cross-sectional survey was conducted on pregnant women between June and August in 2015 in 16 hospitals in five provinces in China. A total of 2345 pregnant women aged 18 years and older were surveyed. Insufficient sleeping duration was defined as sleeping of less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 39 publications
2
26
2
2
Order By: Relevance
“…8 However, the percentage of sleep disorder and sleep disturbances are more in the third trimester of pregnancy. 9 To our dismay, a change in sleep pattern is associated with adverse pregnancy outcomes both in the Venugopal L et al Int J Res Med Sci. 2018 Oct;6 (10): [3197][3198][3199][3200][3201] International Journal of Research in Medical Sciences | October 2018 | Vol 6 | Issue 10 Page 3198 mother and foetus.…”
Section: Introductionmentioning
confidence: 89%
“…8 However, the percentage of sleep disorder and sleep disturbances are more in the third trimester of pregnancy. 9 To our dismay, a change in sleep pattern is associated with adverse pregnancy outcomes both in the Venugopal L et al Int J Res Med Sci. 2018 Oct;6 (10): [3197][3198][3199][3200][3201] International Journal of Research in Medical Sciences | October 2018 | Vol 6 | Issue 10 Page 3198 mother and foetus.…”
Section: Introductionmentioning
confidence: 89%
“…Self-reported quality of sleep [ 33 ] was asked in the following manner: “What is your quality of sleep during the pregnancy?” Response options were very good, good, average, poor, and very poor. Therefore, during data analysis, quality of sleep was divided into three categories: very good or good, average, and poor or very poor.…”
Section: Behavioral Factorsmentioning
confidence: 99%
“…Self-reported secondhand smoke exposure frequency per week [ 33 ] was divided into no exposure, daily, four to six days per week, and one to three days per week. Currently smoking [ 34 ] was defined as those who smoke during pregnancy.…”
Section: Behavioral Factorsmentioning
confidence: 99%
“…Pregnant women with siblings tended to have prolonged TV and computer viewing times. This scenario may indicate the positive influence of siblings on pregnant women in prolonged TV and computer viewing times, and a previous study has also found the influence of siblings on the insufficient sleep of pregnant women in China [ 39 ]. Future studies should focus on pregnant women with siblings and explore the influence of siblings on their family members regarding prolonged screen viewing times and other related health behaviors.…”
Section: Discussionmentioning
confidence: 86%